Kaj je še ostalo od posebnosti postopka v delovnih sporih? - Kogej Dmitrovič, Biserka (Delavci in delodajalci, 2018)
The court procedure for the resolution of labour disputes is regulated by a special law, the Labour and Social Courts Act which has been in force since 2005. This Act, however, does not regulate the procedure in full; it refers to the provisions of the Civil Procedure Act and thus only regulates the particularities. Since its adoption, the Act has been amended several times and a number of provisions have been removed from it. The paper presents an overview of the still valid provisions governing the particularities of the procedure in individual labour disputes.
Keywords: Civil Procedure Act; individual labour dispute; individualni delovni spori; Labour and Social Courts Act; posebnosti delovnega spora; postopkovne določbe; procedural provisions; the specifics of a labour dispute; zakon o delovnih in socialnih sodiščih; zakon o pravdnem postopku